Adoptive Cell Therapy for Metastatic Melanoma. Issue 1 (January 2017) - Merhavi-Shoham, Efrat; Itzhaki, Orit; Markel, Gal; Schachter, Jacob; Besser, Michal J.
Abstract : Abstract: Adoptive cell therapy (ACT) of tumor-infiltrating lymphocytes (TILs) is a powerful form of immunotherapy by inducing durable complete responses that significantly extend the survival of melanoma patients. Mutation-derived neoantigens were recently identified as key factors for tumor recognition and rejection by TILs. The isolation of T-cell receptor ( TCR ) genes directed against neoantigens and their retransduction into peripheral T cells may provide a new form of ACT. Genetic modifications of T cells with chimeric antigen receptors (CARs) have demonstrated remarkable clinical results in hematologic malignancies, but are so far less effective in solid tumors. Only very limited reports exist in melanoma. Progress in CAR T-cell engineering, including neutralization of inhibitory signals or additional safety switches, may open opportunities also in melanoma. We review clinical results and latest developments of adoptive therapies with TILs, T-cell receptor, and CAR-modified T cells and discuss future directions for the treatment of melanoma.